Illicit over the counter availability and recreational use of Zolpidem by young adults: A letter to the editor - Gull, Abdul Rehman; Afzal, Zubia; Batool, Humna (Journal of the Pakistan Medical Association, 2024)
Dear Editor, Zolpidem is a sedative-hypnotic drug that acts as a Central Nervous System (CNS) depressant by acting on GABA receptors. This drug, brand name Ambien, is prescribed mainly for short-term treatment of sleeping problems. However, recent trials and research also show its efficacy in treating various neurological disorders. It is one of the safest drug choices for insomnia, but like any other drug, it has various side effects that include nausea, vomiting, allergies, dizziness, metallic taste, etc. However, some of the concerning side effects include amnesia, parasomnia, and behaviour changes, including hallucinations, delusions, and depression (1). ‘Ambien Zombie’ was a term coined to describe people under the effect of the medication as they got involved in embarrassing activities including sleepwalking. It is a Schedule 4 drug, which means ‘prescription only medicine’ as it has viable medical use but also a low probability of misuse or abuse. Despite the potentially alarming side effects in addition to dependence, which has been reported several times (1), it is becoming increasingly popular among young adults, including students, to use it for various purposes, including and especially recreational. These purposes are sleep, relief from anxiety or depression, feeling good, getting high, relaxing or zoning out, and out of curiosity, while some also use it to perform better at school (2,3). The calming effect of zolpidem on the brain gives a drugged effect, allowing the person to carry out compulsive activities and behaviour, hence called an ‘Ambien Zombie’ while most of the time, forgetting about it the next day (anterograde amnesia) (4). Even after realising this side of drug use, young adults use it for fun to feel disinhibited, or to achieve a euphoric state without any embarrassment. The issue of concern is the widespread availability of this drug in pharmacies. As it is a class 4 drug, it should be given on a doctor’s prescription only. However, it is unfortunate that this is not being followed, especially in Pakistan. While some pharmacies ask for a prescription, the majority give it away freely to anyone asking for it, be it a student or a young doctor prescribing himself. This was mainly due to nonqualified salesmen in the pharmacies becoming a source of illicit sale practice for nonmedical prescription drug use (5). This easy accessibility of Zolpidem has rendered it to be a recreational drug for the youth. ---Continue